Strengthening policy and institutional framework for conservation and sustainable use of plant genetic resources: National programmes and networks as strategic tools, 1-10 October 2002, Zschortau, Germany: Proceedings of an international workshop - Engels, J.M.M.; Kiambi, D.; Watts, J.; Zoungrana, I.; International Plant Genetic Resources Institute (2004)
Policy and institutional frameworks for the conservation and use of plant genetic resources might be in place in many countries although with a variable degree of effectiveness and efficiency. In particular, the performance of existing organizations and institutions at the management and legal level varies greatly among countries and are in need of further development and strengthening. The 2002 workshop was organized to facilitate a process through which countries can learn from each other's strengths, and collectively develop new ideas for an effective sub-regional collaboration based on the experience of FAO, IPGRI, InWEnt and other German research and capacity building institutions. The workshop was also meant to strengthen existing collaborative arrangements in the sub-region. It brought participants from Eastern African countries together to exchange experiences, acquire additional knowledge and develop new skills that could contribute to the effective and efficient operation of the newly established regional East African Plant Genetic Resources Network (EAPGREN).